Implementasi Sistem Informasi Penggajian Karyawan Berbasis Desktop Pada PT. Virgi Motor Cikarang - Budiarto, Eko (Jurnal SIGMA, 2024)
PT. Virgi Motor Cikarang is a company engaged in the sale of Honda motorcycles, Ahass / Service segment, and sales of Honda motorcycle spare parts. PT VIRGI MOTOR CIKARANG was founded in 2001. In processing employee data, so far using a computerized but simple payroll system using Ms. software. Excel, so that in processing the data there are obstacles to the occurrence of error processes such as calculating overtime pay, salary deductions, employee salaries, allowances, basic salaries and salary reports must be calculated and repeated calculations of each employee. The method used by the author in this study uses the waterfall method which consists of planning, analysis, design, implementation of maintenance. The result of this research is to produce a computerized payroll information system that is given the convenience of providing payroll data information such as employee data information, position data, allowances & payroll data. In the Payroll Data Information System, the author uses data flow diagrams, ERD, and reports using Microsoft Visual Studio 2019 and SQL Server programming for data processing. After the researchers made the Payroll Information System, the authors hope that the work procedures can be easier for the parties involved in PT. Virgi Motor Cikarang.